The ANALYZING THE INTERFERENCE OF PALEMBANGNESE AT THE STUDENTS' ENGLISH PRONUNCIATION BY USING PRAAT SOFTWARE - ersen, anazinia (Journal of Education, Linguistics, Literature and Language Teaching, 2024)
ABSTRACT English is a global language necessary for communication and education. Each language has a unique system of sounds and intonation patterns, and the way English is spoken can differ significantly across the country. In Indonesia, we have another ethnic language, Palembangnese. The objective of this research is 1) To determine whether segmental sounds in students' English pronunciation interfere with Palembangnese as their mother tongue using PRAAT software and 2) To find out the factors causing Palembangnese interference with English pronunciation. This research used a qualitative descriptive method. The researcher designed observation as an instrument to collect and analyze the data. However, during observation, the researcher documented the words. Then, the researcher's data was analyzed using PRAAT software. The participants involved in this study were 20 students at Eleventh Grade SMK YIS Martapura school. The results of the research showed from the data that have been analyzed based on the data that have been taken; there are a few words such as /ðəm/, /ˈevrideɪ/, /ˈfɑːðə(r)/, /sliːp/, /laɪf/, /ˈhɪərəʊ/, /ˈhɒlədi/ this indicates interference when Palembang people pronounce the foreign language, that is the English language. There are some words, such as /ˈfɑːðə(r)/, that change in terms of segmental sounds and meaning. The study discovered that learners demonstrated foreign language impacts, including grammatical features and borrowing. In summary, learning a foreign language (FL) alters learners' first language (Ll), implying that studying English influenced their language "Palembangnese." Learning a second or foreign language may interfere with a learner's primary language. Keywords: English, Pronunciation, Interference, Palembangnese Language, Praat Software